Given f(x)=2^x and g(x)=f(x-3)+4, write the new function rule (equation) for function g and describe (using words*) the two transformations that occur between function f and function g.

Respuesta :

Answer:

  • The first thing we do is find out what f(x-3) is
  • [tex]f(x)=2^x\\f(x-3)=2^{x-3}[/tex] this is can be simplified using the rules of exponents
  • [tex]f(x-3)=2^{x-3}\\f(x-3)=2^x\div2^3\\f(x-3)=\frac{2^{x}}{8}[/tex]
  • Then we put that into g(x)
  • [tex]g(x)=f(x-3)+4\\g(x)=\frac{2^{x}}{8}+4[/tex]
  • The first transformation is at f(x), where it is divided by 8, and then inserted into g(x) which increases the new transformed f(x) by 4